2015
DOI: 10.1590/0004-282x20150008
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway dimensions in patients with craniocervical junction malformations with and without sleep apnea. A pilot case-control study

Abstract: Objective Patients with craniocervical junction malformations (CCJM) tend to suffer more frequently from sleep respiratory disturbances, which are more frequent and severe in patients with basilar invagination. Here we evaluate if patients with CCJM and sleep respiratory disorders (SRD) present smaller airway dimensions than patients without SRD. Method Patients with CCCM with and without sleep respiratory disturbances were evaluated clinically by Bindal's score, modified Mallampati classification, full-night … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…It is possible that corpus callosum hypoplasia can be related to sleep difficulties because the corpus callosum may be implicated in the synchronization of slow waves during sleep . Craniocervical junction abnormalities such as foramen magnum stenosis and cervical canal stenosis, commonly seen in achondroplasia, are also associated with sleep‐related respiratory disturbances . Similar to Harper et al and Macey et al, we also found a number of mixed OSA and CSA patients with an alteration of white matter in the brain and lesions within cerebellar areas, although the clinical significance of these findings remain unclear.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is possible that corpus callosum hypoplasia can be related to sleep difficulties because the corpus callosum may be implicated in the synchronization of slow waves during sleep . Craniocervical junction abnormalities such as foramen magnum stenosis and cervical canal stenosis, commonly seen in achondroplasia, are also associated with sleep‐related respiratory disturbances . Similar to Harper et al and Macey et al, we also found a number of mixed OSA and CSA patients with an alteration of white matter in the brain and lesions within cerebellar areas, although the clinical significance of these findings remain unclear.…”
Section: Discussionsupporting
confidence: 83%
“…26 Craniocervical junction abnormalities such as foramen magnum stenosis and cervical canal stenosis, commonly seen in achondroplasia, are also associated with sleep-related respiratory disturbances. 27,28 Similar to Harper et al 29,30 and Macey et al, 31 we also found a number of mixed OSA and CSA patients with an alteration of white matter in the brain and lesions within cerebellar areas, although the clinical significance of these findings remain unclear. Where some abnormal findings are expected for certain comorbidities, it is also important to confirm or exclude these on a brain MRI to fully understand the etiology of an underlying sleep disorder and deliver the appropriate care to these patients.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, some recent studies have shown alterations in the oropharynx and airway of adult CM-I patients. 19,50…”
Section: Etiology Of Classic Cm-imentioning
confidence: 99%
“…Although the current study found no statistically significant differences in the incidence of sleep apnea between the CCJM types, others indicated that sleep apnea was more frequent and intense in BI patients. [5] In 43 patients with atlantoaxial dislocation and CCJM, Shuhui et al . found the following SS to be prevalent (in descending order): weakness (93%), cervical motor limitations (88%), limb paresthesia (98%), neck and shoulder pain (58%), ataxia (42%), vertigo (23%), and respiratory difficulties (7%).…”
Section: Discussionmentioning
confidence: 99%